Mekanisme Pergantian Antar Waktu (PAW) Anggota Dewan Perwakilan Rakyat dalam Sistem Ketatanegaraan Indonesia - Jon Samuel Sonbay; I Gusti Bagus Suryawan; I Nyoman Sutama (Jurnal Analogi Hukum, 2021)
in article 213 of the Act. No. 27 Of 2009 concerning the authority of Inter-Time Replacement had triggered a polemic because it was eliminated, raising the demands of the public who want accountable board members, both in terms of political performance and ethical behavior. Therefore, PAW itself is resurfaced by being regulated in Law No.13 of 2019. The problems of this study are: 1) How is the mechanism of Inter-Time Turnover of Dpr Members in the Indonesian State System? and 2) What is the existence of Inter-Time Change in the Indonesian democratic system?. The type of research and problem approach used is normative legal research. Primary and secondary sources of legal materials. The collection technique in this study is the library study technique. And collected and analyzed by interpretation. The result of this study is PAW from members of the House of Representatives conducted based on the rule of legal mechanisms stipulated in Law No. 27 of 2009. While the operational implementation is contained in the Regulation of the House of Representatives of the Republic of Indonesia Number 1/DPR RI/I/2009-2010 on The Code of Conduct.